Papillary-cystic neoplasms of the middle ear are distinct from endolymphatic sac tumours - Taverna, Cecilia; Pollastri, Federica; Pecci, Rudi; Giannoni, Beatrice; Fattorini, Caterina; Santucci, Marco; Müller, Sarina Katrin; Stöhr, Robert; Franchi, Alessandro; Agaimy, Abbas (Histopathology, 2020)
Aims Papillary neoplasms of the middle and inner ear are rare and poorly characterised. The current World Health Organization classification divides them into two major subtypes: aggressive papillary tumours (APTs) and endolymphatic sac tumours (ELSTs). The aim of this article is to present two papillary neoplasms of the middle ear that do not fit into either the classic APT category or the classic ELST category, and compare them with three ELSTs.
CRIS-Team WoS Importer:2020-11-27